The effect of education and school quality on female crime - Javier Cano-Urbina; Lance Lochner (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2016)
This paper estimates the effects of educational attainment and school quality on crime among American women. Using changes in compulsory schooling laws as instruments, we estimate significant effects of schooling attainment on the probability of incarceration using Census data from 1960-1980. Using data from the 1960-90 Uniform Crime Reports, we also estimate that increases in average schooling levels reduce arrest rates for violent and property crime but not white collar crime. The estimated reductions in crime for women are smaller in magnitude than comparable estimates for men; however, the effects for women are larger in percentage terms (relative to baseline crime rates). Our results suggest small and mixed direct effects of school quality (as measured by pupil-teacher ratios, term length, and teacher salaries) on incarceration and arrests. Finally, we show that the effects of education on crime for women is unlikely to be due to changes in labor market opportunities and may be more related to changes in marital opportunities and family formation.
Keywords: 330